Changes in heart rate variability and hemodynamics of adolescents within the frontal cortex in response to face emotional stimulation - Sung Ah Chung; Hyunchan Hwang; Hee Jin Kim; Ji Sun Hong; Sun Mi Kim; Doug Hyun Han (PLoS ONE, 2025)
Background Functional near-infrared spectroscopy (fNIRS) and heart rate variability (HRV) are commonly utilized biomarkers for assessing emotional states. This study hypothesizes that emotional perception—particularly the experience and variability of unpleasant emotions in adolescents—may be characterized by reduced HRV and increased or dysregulated frontal lobe activity, indicative of impaired emotional and autonomic regulation. Materials and Methods A total of 55 adolescents were enrolled in this study. After completing clinical questionnaires, resting-state HRV and fNIRS data were collected from all participants over a 200-second period. Following a 10-second intermission, HRV and fNIRS were simultaneously recorded during a 192-second positive emotional perception task. After a subsequent 30-second rest, the same procedures were repeated during a negative emotional perception task. Results A higher correction rate of unpleasant facial emotional perception—defined as the proportion of emotional stimuli (positive, negative, and neutral expressions) interpreted as unpleasant—was significantly associated with reduced HRV, as evidenced by lower high-frequency (HF) power and decreased standard deviation of normal-to-normal intervals (SDNN). Moreover, this correction rate positively correlated with the differential accumulation of oxygenated hemoglobin (ΔaccHbO₂) in the left dorsolateral prefrontal cortex (DLPFC), suggesting increased cortical engagement during the processing of negatively perceived stimuli. In contrast, the correction rate of pleasant facial emotional perception showed a negative correlation with ΔaccHbO₂ in the same region. Additionally, both unpleasant-SDNN and unpleasant-HF values were negatively correlated with ΔaccHbO₂ in the left DLPFC. Conclusions In adolescents, the perception of negative emotions is associated with individual differences in depression and anxiety levels. Furthermore, the perception of negative emotions demonstrates significant associations with alterations in HRV and neural activity within the left DLPFC. These findings also support a potential relationship between autonomic function and frontal lobe activation during the processing of unpleasant emotional stimuli.